SAT0314 TIMED FUNCTION TESTS ARE AN ALTERNATIVE TO MMT8 AND FI-2 IN INFLAMMATORY MYOSITIS - AN OBSERVATIONAL COHORT STUDY. (2nd June 2020) - Dunga, S. K.; M B, A.; Kavadichanda, C.; Negi, V.
Abstract : Background: Inflammatory myositis are heterogenous group of diseases affecting skeletal muscles and multiple different organs 1 . Manual muscle testing (MMT) is the common tool used for assessment of muscle strength. Its limitations include poor sensitivity to change, floor/ceiling effect, and under representation of certain important muscle groups 2 . Functional index 2(FI-2) is an objective measure of dynamic repetitive muscle function at 11 proximal and distal muscle groups which correlates well with patient-reported physical function 3 . Since MMT8 is inadequate and FI-2 takes longer time to administer, several timed tests to assess muscle function, endurance and fatiguability like the 2- minute walk test (2MWT) or 30s raise from a chair test and 30s arm rise test are viable alternatives to be tested. Data looking at the performance of these tests are limited to small controlled studies. Objectives: To study correlation of timed tests with MMT8 and FI-2 in assessing muscle strength, endurance at baseline and at 3 months of therapy. Methods: An observational cohort study, included 19 patients with polymyositis and dermatomyositis attending OPD and IPD service of tertiary center. Patients with nclusion body myositis, overlap myositis, chronic kidney disease, coexisting myocarditis, sepsis, malignancy, pregnancy were excluded. MMT8, FI-2 and Timed function tests were done at baseline and after 3 months. Results: The study had 19 patients of which 6 were polymyositis and 13 were dermatomyositis. Male to female ratio was 1:2.1. Anti-cell antibody was positive in 16 patients. The mean MMT8 of the study group at baseline was 60.84±16.77 and after 3 months was 67.05±11.7. Out of 19 patients, all received prednisolone as induction agent followed by Methotrexate in 13, cyclophosphamide in 9, azathioprine in 5, Rituximab by one patient. Mean scores of 30s arm lift, 30s rise from chair test and 2 min walk test were 11.7±6.39, 14±7.29, 101.5± 46.48 respectively at baseline and 13.05±6.5, 15.6±7.1, 117.84±38.4 after 3 months. Conclusion: Timed function tests correlated well with MMT 8 and parameters with in FI-2. Thus these tests are good alternatives in assessing disease activity and response assessment in inflammatory myositis. References: [1]Selva-O'Callaghan A, Pinal-Fernandez I, Trallero-Araguás E, Milisenda JC, Grau-Junyent JM, Mammen AL. Classification and management of adult inflammatory myopathies. Lancet Neurol. 2018; 17:816–28. [2]Rider LG, Aggarwal R, Machado PM, Hogrel J-Y, Reed AM, Christopher-Stine L, et al. Update on outcome assessment in myositis. Nat. Rev. Rheumatol. 2018;14:303–18. [3]Alexanderson H, Broman L, TollbÄck A, Josefson A, Lundberg IE, StenstrÖm CH. Functional index-2: Validity and reliability of a disease-specific measure of impairment in patients with polymyositis and dermatomyositis. Arthritis Rheum. 2006;55:114–22. Disclosure of Interests: None declared